Outcomes and Predictors of Toxicity after Selective Internal Radiation Therapy Using Yttrium-90 Resin Microspheres for Unresectable Hepatocellular Carcinoma - Gabrielson, Andrew; Miller, Akemi; Banovac, Filip; Kim, Alexander; He, Aiwu Ruth; Unger, Keith (Frontiers in Oncology, 2015)
Purpose: We sought to report outcomes and toxicity in patients with hepatocellular carcinoma (HCC) who received resin Yttrium-90 Selective Internal Radiation Therapy (90Y-SIRT), and to identify factors associated with declining liver function. Methods: Patients treated with 90Y-SIRT were retrospectively evaluated. Radiographic response was assessed using RECIST 1.1. Median liver progression-free survival (LPFS) and overall survival (OS) were calculated using the Kaplan-Meier method. Bivariate analysis was used to examine associations between change in Child-Pugh (CP) score/class and patient characteristics and treatment parameters. Results: Twenty-seven patients with unresectable HCC underwent SIRT, 52% were CP Class A, 48% were Class B; 11% were BCLC stage B, 89% were stage C. Forty-four percent of patients had portal vein thrombus at baseline. One-third of patients received bilobar treatment. Median activity was 32.1 mCi (range 9.18 – 43.25) and median absorbed dose to the liver was 39.6 Gy (range 13.54 – 67.70). Median LPFS and OS were 2.5 and 11.7 months, respectively. Three-month disease control rate was 63% and 52% in the target lesions and whole liver, respectively. New onset or worsened from baseline clinical toxicities were confined to Grade 1-2 events. However, new or worsened Grade 3-4 laboratory toxicities occurred in 38% of patients at 3 months and 43% of patients at 6 months following SIRT (6 had lymphocytopenia, 3 had hypoalbuminemia, 2 had transaminasemia). After 3 months, 6 patients had worsened in CP score and 5 had worsened in class from baseline. After 6 months, 4 patients had worsened in CP score and 1 had worsened in class from baseline. Pretreatment bilirubinemia was associated with a 2+ increase in CP score within 3 months (P = 0.001) and 6 months (P = 0.039) of 90Y-SIRT. Pretreatment transaminasemia and bilirubinemia were associated with increased CP class within 3 months of SIRT (P = 0.021 and 0.009 respectively). Conclusions: 90Y-SIRT was well-tolerated in patients with unresectable HCC, with no Grade 3-4 clinical toxicities. However, Grade 3-4 laboratory toxicities and worsened CP scores were more frequent. HCC patients with pretreatment bilirubinemia or transaminasemia may be at higher risk of experiencing a decline in liver function following 90Y-SIRT.